The house at the end of Ladybug Lane - Primavera, Elise (Robin Corey Books, 2012)
Angelina Neatolini's wish for a pet, denied by her family on the grounds that pets are too messy, is overheard by a hard-of-hearing ladybug, who fills their tidy new home with assorted pests.